Adaptation and Validation of a Droplet Digital PCR Assay for the Detection of Cryptosporidium spp. and Giardia duodenalis in Buffalo Milk - Andrea Mancusi; Yolande Thérèse Rose Proroga; Orlandina Di Maro; Irene Dini; Carlo Grassi; Esterina De Carlo; Orlando Paciello; Gabriele Di Vuolo; Antonio Bosco; Laura Rinaldi; Giovanna Cappelli (Food Control, 2026)

Advanced geophysical data analysis and 3D surveys for the detection and characterization of volcanic and karstic caves - Sabrina Grassi; Gabriele Morreale; Gaetano Giudice; Danilo Messina; Gabriele Quattrocchi; Pietro Monforte; Sebastiano Imposa (Remote Sensing Applications: Society and Environment, 2026)

Effect of chest physiotherapy on cystic fibrosis sputum nanostructure: an experimental and theoretical approach - Michela Abrami; Massimo Maschio; Massimo Conese; Marco Confalonieri; Francesco Salton; Fabio Gerin; Barbara Dapas; Rossella Farra; Alessandra Adrover; Gesmi Milcovich; Claudia Fornasier; Alice Biasin; et al. (Drug Delivery and Translational Research, 2022)
Cystic fibrosis (CF) is a disease characterized by the production of viscous mucoid secretions in multiple organs, particularly the airways. The pathological increase of proteins, mucin and biological polymers determines their arrangement into a three-dimensional polymeric network, affecting the whole mucus and impairing the muco-ciliary clearance which promotes inflammation and bacterial infection. Thus, to improve the efficacy of the drugs usually applied in CF therapy (e.g., mucolytics, anti-inflammatory and antibiotics), an in-depth understanding of the mucus nanostructure is of utmost importance. Drug diffusivity inside a gel-like system depends on the ratio between the diffusing drug molecule radius and the mesh size of the network. Based on our previous findings, we propose the combined use of rheology and low field NMR to study the mesh size distribution of the sputum from CF patients. Specifically, we herein explore the effects of chest physiotherapy on CF sputum characteristic as evaluated by rheology, low field NMR and the drug penetration through the mucus via mathematical simulation. These data show that chest physiotherapy has beneficial effects on patients, as it favourably modifies sputum and enhances drug penetration through the respiratory mucus. Graphical abstract

Geophysical surveys integrated with rainfall data analysis for the study of soil piping phenomena occurred in a densely urbanized area in eastern Sicily - Graziano Patti; Sabrina Grassi; Gabriele Morreale; Mauro Corrao; Sebastiano Imposa (Natural Hazards, 2021)
The occurrence of strong and abrupt rainfall, together with a wrong land use planning and an uncontrolled urban development, can constitute a risk for infrastructure and population. The water flow in the subsoil, under certain conditions, may cause underground cavities formation. This phenomena known as soil piping can evolve and generate the surface collapse. It is clear that such phenomena in densely urbanized areas represent an unpredictable and consistent risk factor, which can interfere with social activities. In this study a multidisciplinary approach aimed to obtain useful information for the mitigation of the risks associated with the occurrence of soil piping phenomena in urban areas has been developed. This approach is aimed at defining the causes of sudden soil subsidence events, as well as the definition of the extension and possible evolution of these instability areas. The information obtained from rainfall data analysis, together with a study of the morphological, geological and hydrogeological characteristics, have allowed us to evaluate the causes that have led to the formation of soil pipes. Furthermore, performance of 3D electrical resistivity surveys in the area affected by the instability have allowed us to estimate their extension in the subsoil and identifying the presence of further areas susceptible to instability.

Combined Used of Rheology and LF-NMR for the Characterization of PVP-Alginates Gels Containing Liposomes - Giulia Fanesi; Michela Abrami; Francesca Zecchin; Irina Giassi; Elena Dal Ferro; Anja Boisen; Gabriele Grassi; Paolo Bertoncin; Mario Grassi; Paolo Marizza (Pharmaceutical Research, 2018)

Environmental quality and hygienic safety of the Alimini Lakes (Puglia, Italy): 20 years of monitoring (1995–2014) - Antonella De Donno; Francesco Bagordo; Francesca Serio; Tiziana Grassi; Gabriele Devoti; Marcello Guido (Rendiconti Lincei. Scienze Fisiche e Naturali, 2017)

Genetic structure of Rhamnus glaucophylla Sommier endemic to Tuscany - Gianni Bedini; Angelino Carta; Giovanni Zecca; Fabrizio Grassi; Gabriele Casazza; Luigi Minuto (Plant Systematics and Evolution, 2011)

Inhibitory effects of fenofibrate on apoptosis and cell proliferation in human endothelial cells in high glucose - Michela Zanetti; Alessia Stocca; Barbara Dapas; Rossella Farra; Laura Uxa; Alessandra Bosutti; Rocco Barazzoni; Fleur Bossi; Carlo Giansante; Francesco Tedesco; Luigi Cattin; Gianfranco Guarnieri; et al. (Journal of Molecular Medicine, 2008)

Connective tissue growth factor: a crucial cytokine-mediating cardiac fibrosis in ongoing enterovirus myocarditis - Christine Lang; Martina Sauter; Gudrun Szalay; Giorgia Racchi; Gabriele Grassi; Giuseppe Rainaldi; Alberto Mercatanti; Florian Lang; Reinhard Kandolf; Karin Klingel (Journal of Molecular Medicine, 2008)